HPB P50 Prediction and Management of Choledocholithiasis in Gallstone Related Disease. (7th December 2022) - Saxena, Shreya; Stevens, Lewis; Mathieson, Georgia
Abstract: Background: Acute cholecystitis, pancreatitis and cholangitis are common presentations to the general surgery on-call shift, the management of which can be complicated by evidence of choledocholithiasis. Risk scoring systems exist to help guide the requirement for further imaging or endoscopy for these patients. Our audit reviewed the American Society for Gastrointestinal Endoscopy (ASGE) scoring system for choledocholithiasis prediction and associated management guidelines against current practices at a tertiary hospital to assess how well common practice matches guideline recommendations based on choledocholithiasis risk. Our aim was to assess how current practice for investigation of possible choledocholithiasis interlinks with CBD stone risk scoring systems, whether risk scoring is useful in management of a gallstone related disease risk and if a choledocholithiasis risk prediction tool could optimize resource usage. Methods: We retrospectively identified a cohort of patients presenting acutely to the surgical unit over a three-month period with symptoms suggestive of cholecystitis, cholangitis or pancreatitis. Patients were identified from prospectively maintained, electronic records of surgical in-patients and on-call surgical patient lists. Patients meeting local guideline criteria for diagnosis of pancreatitis (serum lipase greater than 3 times the upper limit of normal or CT confirmed pancreatic inflammation) or Tokyo Guidelines 2018 for diagnosis of cholecystitis and cholangitis were included. Those with non-gallstone pathology, previous cholecystectomies and incomplete data were excluded. Patients were categorized into respective risk strata according to the ASGE scoring system and their ongoing management was compared against those guidelines. Subgroup analyses on outcomes and complications for those in each risk strata and in those with age over 55 years of elevated bilirubin as risk factors were also performed. Results: 78 patients were identified with 13 categorized as high-risk, 46 intermediate risk and 19 low-risk. 12 of 13 patients (92%) at high risk had evidence of choledocholithiasis on MRCP, CT or USS. 10 of 12 patients (83%) subsequently had a definitive ERCP or preceding cholecystectomy. No low-risk patient had evidence of choledocholithiasis on imaging. 90% of this group have had or are awaiting cholecystectomy. 1 patient, who declined cholecystectomy, re-presented 8 months later with choledocholithiasis. Within the intermediate risk category, there was greater discrepancy in the predictive value of choledocholithiasis. 17 of 46 (37%) patients had an MRCP or EUS with 4 having choledocholithiasis and all going on to have duct clearance. 29 patients (63%) did not have MRCP or EUS, instead receiving either USS, CT or both. 2 patients in this group were unfit for further procedure and received no further imaging, 2 patients had evidence of choledocholithiasis and 25 had no evidence of choledocholithiasis. To date 12 patients have had or are awaiting a cholecystectomy and a further 12 have declined or were not fit for cholecystectomy. 8 patients were stratified as intermediate risk on age >55 alone with no patients having evidence of choledocholithiasis. Conclusions: Although based on a small retrospective study, risk prediction using the ASGE scoring tool works effectively in high and low risk patient cohorts, but appears to over predict choledocholithiasis in the intermediate risk group, particularly when based on age alone. Patients with high risk of choledocholithiasis should proceed to duct clearance without further imaging, whilst low risk patients can proceed directly to cholecystectomy. Over investigation dictated by the guidelines for the intermediate risk group is likely to lead to poor compliance as shown in our dataset and may lead to increased burden on imaging services, particularly in hospitals serving more elderly populations.